The family business in new EU countries: the spread and agency conflicts they face - Sapkauskiene, Alfreda; Sileikiene, Liliana (Buhalterinės apskaitos teorija ir praktika, 2019)
Capital financing is vital for the development of the new EU countries. Investors base their economic and financial decisions on the information available in the financial reports that listed EU companies must prepare following International Financial Reporting Standards (IFRS). Studies show that the majority of listed companies worldwide are family owned and face Type II agency problem - the conflict between minority shareholders and large controlling shareholders (family), i.e. controlling family may seek to extract private benefits at the expense of minority shareholders and disclose information in financial reports for self-interested purposes to avoid minority contests. The research of Type II agency conflict effects on mandatory IFRS disclosure levels in the new EU countries is limited, however, with the reference to existing research literature and legal systems in the new EU countries, we find that minority protection is strongest in Malta, and weakest in Latvia. The biggest number of family controlled firms are in Poland and Romania, whilst family business in Poland, Estonia, Croatia, Cyprus, Romania and Bulgaria enjoy the largest market capitalisation. Nationally, the highest market capitalisation of family controlled firms are in Estonia, Cyprus, Latvia and Poland. This paper shows, that due to moderate minority protection in the new EU countries Type II agency conflict is important, and therefore, it is suggested further the research related to mandatory IFRS disclosure levels.